"¿Quen Manda?" (Who’s in Charge?): Household Authority Politics in Rural Galicia - Roseman, Sharon R. (Anthropologica, 2022)
This paper focusses on the intricate contours of household authority politics in Zas, a rural township located in the Spanish Galician province of A Coruna. My main argument is that individuals living in this part of Atlantic Spain draw on the discursive themes of both social hierarchy and egalitarianism in continually negotiating their own positions and those of their co-resident kin. I illustrate this dynamic by providing ethnographic examples from three stem-family households. My inclusion of the question "Who’s in Charge?" as part of the title to this paper refers to my general challenge to overly structural models of authority politics for analyses of family relationships.